Can the private sector lead agricultural mechanization in Ghana? - Houssou, Nazaire; Diao, Xinshen; Kolavalli, Shashidhara (International Food Policy Research Institute, 2014)
Increasing agricultural mechanization has long been of interest to many African countries. Constrained by the limited area that can be cultivated through the use of the hand hoe and its association with perceptions of primitiveness and drudgery, agricultural mechanization and large-scale farming have long been a part of the vision of modernizing agriculture in many African countries, including Ghana.